Feminist Perspective of Life’s Struggle: A Literature Review of the Movie Little Woman (2019) - Samad, Pratiwi; Paris, Nirma (Innovations in Language Education and Literature, 2024)
This study delves into the challenges contemporary women face, particularly in negotiating societal expectations, spiritual support in relationships, and the balance between education, career, and marriage. Through an analysis of the characters Jo and Amy in Greta Gerwig's "Little Women," it aims to explore these complexities and offer insights into modern women's perspectives on life. The research draws on the film "Little Women" (2019) and a range of literary sources, including research papers, journals, and publications. By examining the educational backgrounds, marital experiences, motivations, and thoughts of Jo and Amy, the study investigates the nuanced struggles and aspirations of women in different facets of life. The findings reveal that feminist ideology intersects with various dimensions of women's struggles, encompassing aspirations for freedom, education, marital rights, and happiness. Jo and Amy confront significant obstacles reflective of 19th-century challenges, compounded by societal norms that tethered women's happiness to male support, hindering their pursuit of independence. The study emphasized the continuing relevance of the discourse of feminists by exposing the challenges faced by women in Little Woman. Through an exploration of Jo and Amy's journeys, it emphasizes the ongoing struggle for autonomy and fulfillment in women's lives across historical contexts.